Private sector takes the lead in adapting CSA tools for the Ivorian cocoa sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Based on project work in Ghana, Rainforest Alliance has expanded this work into Ivory Coast through connections with ICRAF and the World Cocoa Foundation. The goal is to provide exposure maps and specific CSA practice guidance to Ivorian farmers similar to what is available in Ghana in the form of training materials, training of company extension officers and farmers and the translation of the Cocoalink app into French.